Estudo comparativo da qualidade de amostras de camarão-branco-do-pacífico (Penaeus vannamei), pré-cozidas pelo método de aquecimento convencional e ôhmico - Sousa, Francisco Ikaro Xavier de (2025)
Brazil is currently one of the fastest-growing countries in terms of aquaculture production, ranking 13th in the world in the production of aquatic organisms, according to FAO in 2022. Among the species most produced in Brazil and most exported to other countries is the Pacific white shrimp (Penaeus vannamei). The methods used to cook this food that are already widespread in the industry, such as steam heating, boiling or the use of scalding water, can lead to changes in the constitutional profile of the food, directly impacting on the profile of lipids and fatty acids, for example, or causing greater losses through cooking. In this context, the aim of this work is to apply the ohmic heating technique to shrimp samples, assessing their quality over a period of prolonged storage. This work evaluated the speed of temperature progression in a conventional heating treatment and an ohmic heating treatment, as well as the rapid freezing of shrimp samples at -30 °C, in order to assess differences between the two techniques and changes in the product during 6 months of storage. For this purpose, physicochemical and microbiological analyses were used, as well as evaluating the centesimal composition and texture of the samples. The results of the temperature progression curves show faster temperature distribution for ohmic heating, which also showed the lowest average cooking losses (7.86%). With regard to quality parameters, the highest averages for oxidation, N-BVT and pH were observed in the treatment with ohmic heating (0.29 mg of MDA/kg of fish, 7.35 and 23.8 mg of N/100 g of fish), but within acceptable limits. Analysis of the centesimal composition showed a decrease in the moisture content of the samples and protein concentration at the end of the experiment for both treatments, suggesting changes with storage. The color analysis suggested an increase in the brightness (L*) of the samples and a slight change in the color patterns (a* and b*). In assessing the microbiological quality of the samples, the two treatments were effective in reducing the amount of colony-forming units in the shrimp (from 4.88 CFU/g in fresh shrimp to 2.71 and 3.25 CFU/g respectively for conventional and ohmic heating at the end of 6 months). Changes in texture parameters were observed in both treatments, with small variations in hardness, chewiness and maintenance of product elasticity. Further tests should be carried out to improve the use of ohmic heating in fish samples.